If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 5)(n + -5) = 12 Reorder the terms: (5 + n)(n + -5) = 12 Reorder the terms: (5 + n)(-5 + n) = 12 Multiply (5 + n) * (-5 + n) (5(-5 + n) + n(-5 + n)) = 12 ((-5 * 5 + n * 5) + n(-5 + n)) = 12 ((-25 + 5n) + n(-5 + n)) = 12 (-25 + 5n + (-5 * n + n * n)) = 12 (-25 + 5n + (-5n + n2)) = 12 Combine like terms: 5n + -5n = 0 (-25 + 0 + n2) = 12 (-25 + n2) = 12 Solving -25 + n2 = 12 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + n2 = 12 + 25 Combine like terms: -25 + 25 = 0 0 + n2 = 12 + 25 n2 = 12 + 25 Combine like terms: 12 + 25 = 37 n2 = 37 Simplifying n2 = 37 Take the square root of each side: n = {-6.08276253, 6.08276253}
| h^4+12=7h^2 | | 8ab^2-12ab=0 | | 13-x=9-x | | w-1/4u=0 | | 3x^(2/5)-5=22 | | (10-x)-3=1 | | 4a+4c=52 | | -112/22 | | 4r+8=8-16r | | 6=-3x+59 | | 7+3x+8= | | 4x^2-31x+18=-8x+3 | | W-1/4u | | (8x+5)=(3x+10) | | 4p+5q=14 | | 4.2x=12.25 | | rts=qk | | 16x^2-80x-100-(9x^2+6x+1)=0 | | (7/11)^2 | | 3x+26=7(x-6) | | 144/3=76 | | y=-9x+12 | | 4/5x=x-32 | | 5-2x=6x-3 | | 2/3x0=5 | | 4(4x^2-20x+25)-(9x^2+6x+1)=0 | | x*10+30=x*6+126 | | 4=-2(1/2*-1) | | 5x+14=30-6x | | 4=-2(1/2*-1 | | 2.75x=.35x+12000 | | P=b+2a |